INFORMATION SYSTEM FOR AUTOMATED SERVICES OF SMALL BUSINESSES - NIKONOV, OLEH; SKIDAN, VLADYSLAVA; VOLIVACH, ANTONINA; SATAYEV, MARAT (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The purpose of this work is to research information systems for automated services of small businesses based on the use of mobile software applications to enhance their efficiency and competitiveness. Enhancing efficiency and competitiveness is a primary trend in the development of small businesses in modern business ecosystems. In the face of increasing competition and rapid changes in business ecosystems, companies are improving their processes using new technologies and strategies that open up new opportunities for growth and development, as well as ensure their resilience in business ecosystems. The automation of services for small businesses is a development direction that contributes to increasing their efficiency and competitiveness. This work investigates information systems for automated services of small businesses based on the use of mobile software applications, using service sector companies as an example. Based on the analysis of existing mobile applications for service-oriented businesses, a mobile application of an automated system «Digital Device Repair» has been developed using Microsoft Visual Studio tools. The developed configuration consists of three functional subsystems, implementing multi-level access rights to functional components and ensuring optimized handling of customer orders. A three-tier architecture is chosen for the development of the mobile application software system, which includes components: a client application connected to an application server, which is in turn connected to a database server. A functional model of an information system for automated services for small businesses has been developed using the example of the mobile application «Digital Device Repair».